Estimating the global conservation status of more than 15,000 Amazonian tree species - ter Steege, Hans; Pitman, Nigel C.A.; Killeen, Timothy J.; Laurance, William F.; Peres, Carlos A.; Guevara, Juan Ernesto; Salomão, Rafael P.; Castilho, Carolina V.; Amaral, Ieda; de Almeida Matos, Francisca Dionízia; de Souza Coelho, Luiz; Magnusson, William E.; et al. (American Association for the Advancement of Science, 2015)
Estimates of extinction risk for Amazonian plant and animal species are rare and not often incorporated into land-use policy and conservation planning. We overlay spatial distribution models with historical and projected deforestation to show that at least 36% and up to 57% of all Amazonian tree species are likely to qualify as globally threatened under International Union for Conservation of Nature (IUCN) Red List criteria. If confirmed, these results would increase the number of threatened plant species on Earth by 22%. We show that the trends observed in Amazonia apply to trees throughout the tropics, and we predict thatmost of the world’s >40,000 tropical tree species now qualify as globally threatened. A gap analysis suggests that existing Amazonian protected areas and indigenous territories will protect viable populations of most threatened species if these areas suffer no further degradation, highlighting the key roles that protected areas, indigenous peoples, and improved governance can play in preventing large-scale extinctions in the tropics in this century.